Short communication: susceptibility of culex sitiens to Japanese encephalitis virus in peninsular Malaysia - Vythilingam, Indra; Tan, S.B.; Krishnasamy, M. (Wiley, 2002)
The susceptibility of Culex sitiens to Japanese Encephalitis (JE) virus was examined in the laboratory. Cx. sitiens became infected with JE virus on day 8 and subsequently it is able to transmit the virus when it takes a blood meal. Both parts of the experiment were carried out using artificial membrane feeding technique.